Targeting Premature Renal Aging: from Molecular Mechanisms of Cellular Senescence to Senolytic Trials - Franzin, Rossana; Stasi, Alessandra; Ranieri, Elena; Netti, Giuseppe Stefano; Cantaluppi, Vincenzo; Gesualdo, Loreto; Stallone, Giovanni; Castellano, Giuseppe (Frontiers in Pharmacology, 2021)
The biological process of renal aging is characterized by progressive structural and functional deterioration of the kidney leading to End-stage renal Disease, requiring renal replacement therapy. Since the discovery of pivotal mechanisms of senescence such as cell cycle arrest, apoptosis inhibition and the development of a senescence associated secretory phenotype (SASP), efforts in the understanding of how senescent cells participates in renal physiological and pathological aging have grown exponentially. This has been encouraged by both preclinical studies in animal models with senescent cell clearance or genetic depletion as well as due to evidence coming from the clinical oncologic experience. This review considers the molecular mechanism and pathways that trigger premature renal aging from mitochondrial dysfunction, epigenetic modifications to autophagy, DNA Damage Repair (DDR) and the involvement of extracellular vesicles. We also discuss the different pharmaceutical approaches to selectively target senescent cells (namely senolytics) or the development of systemic SASP (called senomorphics) in basic models of CKD and clinical trials. Finally, an overview will be provided on the potential opportunities for their use in renal transplantation during ex vivo machine perfusion to improve the quality of the graft.